(untitled) (Journal of Biomedical Investigation, 2025)
Background: Atherogenic dyslipidaemia and the risk of CVD in type 2 diabetics has been widely investigated. Few studies in Nigeria have been carried out among different ethnic groups to understand the pattern of dyslipidaemia and its link with hyperglycaemia in type 2 diabetics. Aim: The present study aimed to determine the influence of hyperglycaemia on the lipid profile parameters in type 2 diabetes of the three major ethnic groups in Nigeria. Materials and Methods: This was a cross-sectional study in which Blood glucose and lipid profile parameters were determined using standard laboratory tests. Ranges for TC < 200 mg/dl, TG < 150 mg/dl, LDL-C < 100 mg/dl, 51-60 mg/dl for females, and HDL-C 41- 60 mg/dl for males were considered dyslipidaemia. One-way analysis of variance (ANOVA) followed by Bonferroni multiple comparison test to evaluate the mean difference among the groups. Independent samples t-test was used to evaluate the mean difference in FBG and BMI with lipid profiles between groups. Analysis was with statistical significance set at <0.05. Results: The FBS was associated with increased TC, TG and LDL-c (r = 0.483269, 0.623952 and 0.390193 respectively). Similarly, BMI was found to be associated with increased TC, TG and LDL-c (r=0.432284, 0.569792 and 0.339701 respectively) with p=0.000001) However, both FBS and BMI were associated with decreased serum HDL-c levels (r= -0.278993 and -0.247900 respectively) with p=0.000001. Correlation between FBG and serum lipid profile parameters was observed. FBS levels were positively linked with TG, TC, and LDL-c but negatively associated with HDL-c. Conclusion: A correlation between FBG and serum lipid profile parameters has been observed. FBS levels were positively linked with TG and TC, but negatively associated with HDL-C, the good cholesterol. It can be suggested that failure to control type 2 diabetes leads in dyslipidaemia. Thus, effective control of hyperglycaemia in type 2 diabetics and periodic check and treatment of dyslipidaemia can prevent associated adverse health outcomes.